Quantifying robustness of CT-ventilation biomarkers to image noise - Flakus, Mattison J.; Wuschner, Antonia E.; Wallat, Eric M.; Shao, Wei; Shanmuganayagam, Dhanansayan; Christensen, Gary E.; Reinhardt, Joseph M.; Li, Ke; Bayouth, John E. (Frontiers in Physiology, 2023)
Purpose: To quantify the impact of image noise on CT-based lung ventilation biomarkers calculated using Jacobian determinant techniques. Methods: Five mechanically ventilated swine were imaged on a multi-row CT scanner with acquisition parameters of 120kVp and 0.6mm slice thickness in static and 4-dimensional CT (4DCT) modes with respective pitches of 1 and 0.09. A range of tube current time product (mAs) values were used to vary image dose. On two dates, subjects received two 4DCTs: one with 10mAs/rotation (low-dose, high-noise) and one with CT simulation standard of care 100mAs/rotation (high-dose, low-noise). Additionally, ten intermediate noise level breath-hold (BHCT) scans were acquired with inspiratory and expiratory lung volumes. Images were reconstructed with and without iterative reconstruction (IR) using 1 mm slice thickness. The Jacobian determinant of an estimated transformation from a B-spline deformable image registration was used to create CT-ventilation biomarkers estimating lung tissue expansion. 24 CT-ventilation maps were generated per subject per scan date: four 4DCT ventilation maps (two noise levels each with and without IR) and twenty BHCT ventilation maps (ten noise levels each with and without IR). Biomarkers derived from reduced dose scans were registered to the reference full dose scan for comparison. Evaluation metrics were gamma pass rate (Γ) with 2 mm distance-to-agreement and 6% intensity criterion, voxel-wise Spearman correlation (ρ) and Jacobian ratio coefficient of variation (CoV_JR). Results: Comparing biomarkers derived from low (CTDI_vol=6.07mGy) and high (CTDI_vol=60.7mGy) dose 4DCT scans, mean Γ, ρ and CoV_JR values were 93%±3%, 0.88±0.03 and 0.04±0.009, respectively. With IR applied, those values were 93%±4%, 0.90±0.04 and 0.03±0.003. Similarly, comparisons between BHCT-based biomarkers with variable dose (CTDI_vol=1.35-7.95mGy) had mean Γ, ρ and CoV_JR of 93%±4%, 0.97±0.02 and 0.03±0.006 without IR and 93%±4%, 0.97±0.03 and 0.03±0.007 with IR. Applying IR did not significantly change any metrics (p>0.05). Discussion: This work demonstrated that CT-ventilation, calculated using the Jacobian determinant of an estimated transformation from a B-spline deformable image registration, is invariant to Hounsfield Unit (HU) variation caused by image noise. This advantageous finding may be leveraged clinically with potential applications including dose reduction and/or acquiring repeated low-dose acquisitions for improved ventilation characterization.